A low-cost and eco-friendly network binder coupling stiffness and softness for high-performance Li-ion batteries. (10th August 2021) - Zhao, Erying; Guo, Zonglei; Liu, Jie; Zhang, Qian; Guo, Ziyang; Yang, Yu; Wang, Hui; Wang, Lei
Highlights: A new network binder coupling of stiffness and softness has been designed. The highly elastic XNBR is firstly used to construct robust binder for Si anode. The new network binder has good compatibility for both Si anode and LiFePO4 cathode. Abstract: High-energy-density Li-ion batteries are urgently demanded in the development of electric vehicles and smart power grids. Owing to the high theoretical capacity, silicon (Si) has been considered as one of the most promising anode materials for next-generation Li-ion batteries. However, Si anode materials undergo huge volume change during charge and discharge processes, which severely impairs the cycle stability of Si anodes. Herein, to stabilize the Si anodes, a low-cost and eco-friendly network binder coupling hardness with softness was designed through in-situ cross-linking of guar gum (GG) and carboxylated acrylonitrile-butadiene rubber (XNBR). The rigid and high-viscosity GG functions as a skeleton to withstand the expansion of Si active materials, and the elastic XNBR can effectively buffer the residual stress. The mass ratio of GG and XNBR was systematically studied to achieve superior cycling stability of Si anodes. Especially, the Si@X4G6 electrode shows excellent cycle stability, remaining a capacity of 1929 mAh g   −   1 at 1000 mA g   −   1 after 100 cycles. Interestingly, such an effective strategy not only works well in Si anodes but also does well in Si/C anodes and LiFePO4 cathodes.